The crime of exploiting children in prostitution via internet (legal study) - Yaseen Al-Shwani, Nawzad Ahmed; Shaker Mahmood, Ibrahim (Journal of the University of Zulia, 2020)
The crime of exploiting children in prostitution is considered as one of the most dangerous sexual crimes since it forms a material and moral violence at the same time. So, the promotion for the pornographic data for gratifying the sexual instincts for the others, or for getting trade profits becomes a familiar thing in the internet where the child can be offended including showing photos and pornographic movies having photos for minor female children or photos and movies for the processes of the sexual torture and the sexual organs and the rape processes or the sexual processes exerted against the minor children. Because of the expansion of this crime owing to the bad use of the technological development, it is needed to put a limit for this by activating the national and international laws and putting it in an executive position especially it has not received enough interest. So, it must have the interest it deserves in a form that obligates the all, individuals and governments, and imposing suitable penalties against the ones who violate the rights of the child. The Iraqi project must go along with the technological develops by putting a special law for this purpose. Next we will analyze the pillars of the crime of exploitation of children in prostitution and study the penalty related to the crime of exploitation of children in prostitution, especially in Iraq.